Análise de desempenho de relés de proteção com hardware process bus - Melo, Andre Felipe Silva (2021)
The pursuit for new technologies to make the substation automation systems (SAS) more efficient is continuous. The IEC 61850 standards have ensured the continuous improvement of the power system management at different levels, the part 9-2 of the standard defines the sampled values protocol’s profile and joint with it the possibility of the replacement of the conventional measurement method by an ethernet-based system called process bus. The implementation of the process bus relies not only on changing the conventional switchyard instrumentation but the adaptation of the intelligent electronic device’s architecture to the new kind of data input. This research focuses on the investigation of the effects of the PB implementation over the protection relays performance such as increasing trip time, measurement, and possible phase shift. This research presents aspects that must be considered through the engineering process and design, considering when using PB according to IEC61850- 9-2LE and IEC61869-9. The investigations were performed using a test architecture composed of a distance conventional relay and two PB relays of the same model, regarding time synchronization, the devices were synchronized via IEEE1588 (PTP) protocol to guarantee the time accuracy needed. The carried-out study cases include simulation of a transmission line under fault using the ATPDraw software, data collected in the field, such as the inrush curve of a medium voltage transformer and the trip times of a line distance protection. The two PB relays presented similar results during the tests. This work has as major contributions, to present the resampling effect of the SV signal that is not considered by the PB standards, the PB relays present a time shift in the input signal compared to the conventional relay, which impacts analysis and failure detection, especially in mixed systems. The final trip time is increased by approximately 9 ms due to network delay, this delay needs to be considered in protection studies before implementation. Otherwise, it can result in a significant impact on the coordination, selectivity, and lifecycle of assets.